Evaluating the accuracy of ChatGPT in delivering patient instructions for medications: an exploratory case study - Abanmy, Norah Othman; Al-Ghreimil, Nadia; Alsabhan, Jawza F.; Al-Baity, Heyam; Aljadeed, Rana (Frontiers in Artificial Intelligence, 2025)
BackgroundThe use of ChatGPT in healthcare is still in its early stages; however, it has the potential to become a cornerstone in modern healthcare systems. This study aims to assess the accuracy of output of ChatGPT compared with those of CareNotes® in providing patient instructions for three medications: tirzepatide, citalopram, and apixaban.MethodsAn exploratory case study was conducted using a published questionnaire to evaluate ChatGPT-generated reports against patient instructions from CareNotes®. The evaluation focused on the completeness and correctness of the reports, as well as their potential to cause harm or lead to poor medication adherence. The evaluation was conducted by four pharmacy experts and 33 PharmD interns.ResultsThe evaluators indicated that the ChatGPT reports of tirzepatide, citalopram, and apixaban were correct but lacked completeness. Additionally, ChatGPT reports have the potential to cause harm and may negatively affect medication adherence.ConclusionAlthough ChatGPT demonstrated promising results, particularly in terms of correctness, it cannot yet be considered a reliable standalone source of patient drug information.